Temporal anticipation based on memory. - Cravo, A; Rohenkohl, G; Santos, K; Nobre, A (Massachusetts Institute of Technology Press, 2017)
The fundamental role that our long-term memories play in guiding perception is increasingly recognized, but the functional and neural mechanisms are just beginning to be explored. Although experimental approaches are being developed to investigate the influence of long-term memories on perception, these remain mostly static and neglect their temporal and dynamic nature. Here, we show that our long-term memories can guide attention proactively and dynamically based on learned temporal associations. Across two experiments, we found that detection and discrimination of targets appearing within previously learned contexts are enhanced when the timing of target appearance matches the learned temporal contingency. Neural markers of temporal preparation revealed that the learned temporal associations trigger specific temporal predictions. Our findings emphasize the ecological role that memories play in predicting and preparing perception of anticipated events, calling for revision of the usual conceptualization of contextual associative memory as a reflective and retroactive function.